Estimation of adiponectin levels in diabetic, non-diabetic fatty liver diseases and healthy controls - Pandey, Ashish Kumar; Jalihal, Umesh; Kalra, Pramila; Gowda, Vanitha MN.; Prabhu, Vinay MD. (International Journal of Research in Medical Sciences, 2017)
Background:Estimation of adiponectin levels in diabetic and non-diabetic fatty liver and healthy controls. Methods:We studied 25 subjects for diabetic fatty liver, 25 subjects for non-diabetic fatty liver and 25 healthy controls. Clinical evaluation included anthropometric measurements, BMI, biochemical investigations and adiponectin estimation by ELISA. Results: There were 15 males (60%) and 10 (40%)females subjects in the DFL group, 18 males (72%) and 7 females (28%) subjects in the NDFL group and 13 males (52%) and 12 females (48%) subjects in the control group. 80% (20) of the DFL patients and 72% (18) subjects of NDFL group had BMI >25kg/m2. 80% (12 males and 8 females) of subjects in the DFL group and 68% (12 males and 5 females) had a waist circumference that indicated central obesity as per Indian cut-offs (>90 cm for females and >80 cm for males). The mean adiponectin (μg/ml) ± SD levels in DFL were 4.03 ± 0.43, NDFL was 5.01 ± 0.55 and in controls was 7.63 ± 0.66, the difference being statistically significant with P <0.001. The difference in the adiponectin levels was statistically significant between each of the three groups with P <0.001. There was no difference in serum adiponectin levels between males and females in all three groups. Conclusion:The chief conclusion of this study are that serum adiponectin levels are lower in subjects with NAFLD than those without it; adiponectin levels are inversely related to the degree of steatosis in NAFLD, with the lowest levels in more severe forms of steatosis.